2016
DOI: 10.1007/s00737-016-0696-3
|View full text |Cite|
|
Sign up to set email alerts
|

Financial strain and birth weight: the mediating role of psychological distress

Abstract: Purpose The effects of financial strain during pregnancy have received limited attention. In addition, data examining the pathways by which SES indicators contribute to birth weight are lacking. The objective of the current study was to examine the potential pathway of psychological distress in the relationship between financial strain and birth weight. Methods Participants consisted of 138 pregnant women who completed measures assessing financial strain, depressive symptoms, pregnancy-specific distress, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
(69 reference statements)
1
20
1
1
Order By: Relevance
“…This finding is consistent with previous research conducted among pregnant women in the Czech Republic which showed that perceived discrimination was associated with increased odds of postpartum depression [37]. Similarly, a population-based study of young (ages [18][19][20] women in the Midwest region of the U.S. found a positive association between discrimination and depressive symptoms [38]. That study also found a positive association between discrimination and perceived stress [38], which was not observed in our study.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous research conducted among pregnant women in the Czech Republic which showed that perceived discrimination was associated with increased odds of postpartum depression [37]. Similarly, a population-based study of young (ages [18][19][20] women in the Midwest region of the U.S. found a positive association between discrimination and depressive symptoms [38]. That study also found a positive association between discrimination and perceived stress [38], which was not observed in our study.…”
Section: Plos Onesupporting
confidence: 92%
“…Few studies have examined other sources of psychosocial stress, such as caregiving for an ill family member, financial hardship, and job strain, which may also be associated with elevated levels of other stressors and ultimately adverse pregnancy outcomes [19,20]. For example, it is possible that caregivers experience financial strain, and subsequent depression [21], as a result of missed work.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal mental well-being and stress during pregnancy represent critical determinants of pregnancy outcomes and PTB risk. For example, maternal depression and psychological stress may trigger a pro-inflammatory state, doubling the risk of PTB and adverse birth outcomes (27,(41)(42)(43). Maternal depression and anxiety can also negatively impact motherchild bonding and child development in the long term (44)(45)(46).…”
Section: Experience-based and Prospective Interventionsmentioning
confidence: 99%
“…For example, one study among pregnant women in South Africa found food insecurity was associated with depression, substance dependence, and anxiety [18]. Another study conducted in the United States found that nancial strain was positively associated with depressive symptoms, anxiety, perceived stress, and pregnancy-speci c distress, and negatively associated with birth weight; depression mediated the relationship between nancial strain and birth weight [19].…”
Section: Financial Strain and Pregnancymentioning
confidence: 99%